Os sinistrados no trabalho e o direito à reparação: do guião institucional às experiências e interações - Vanessa Rodrigues (Universidade do Porto, 2018)
The present paper seeks to highlight the institutional dimension of the analysis that was developed within the research project "Return to Work after an Accident: Overcoming Obstacles", promoted by the Associação Nacional de Deficientes Sinistrados no Trabalho (ANDST). Combining the cross-reading of legal and administrative documents, legal doctrine, data from a survey by questionnaire, and the testimonies collected through interviews and compiled on journey maps, this paper tries to analytically reconstruct the main moments that constitute a post-sinister path. Thereto it describes the contacts in the institutional approach to reparation, and articulates it with the representations of the victims about their personal cases and the obstacles they have faced.